Stimuli responsive functional polymeric materials for biomedical applications - Demirer, Hatice Betül. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
This work consists of synthesis, structural characterization and evaluation of stimuliresponsive functional polymers and hydrogels designed for biomedical applications. In the first project pH and redox responsive degradable gels and cryogels were synthesized from phosphonate-functionalized poly(-aminoester) macromers as potential materials for tissue engineering applications. Then injectable poly(-aminoester) based hydrogels were fabricated by a facile one-step method and a photosensitizer released from these hydrogels showed promising activity in phtodynamic therapy. Phosphonic acid containing acrylamides were synthesized and evaluated as self-etching dental adhesives. Furthermore, these acrylamides were used to make hydrogels which were then successfully mineralized to make bone-like composite materials. Lastly carboxylic acid-functional crosslinkers were fabricated into hydrogels, and the pH/redox response of these hydrogels were demonstrated through controlled release studies of R6G dye and resorcinol.
Keywords: Polymers in medicine.; Biomedical materials.